Beneficial microbial species and metabolites alleviate soybean oxidative damage and increase grain yield during short dry spells - Moretti, Luiz Gustavo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Bossolani, João William [UNESP]; Calonego, Juliano Carlos [UNESP]; Moreira, Adônis; Garcia, Ariani [UNESP]; Momesso, Letusa [UNESP]; Kuramae, Eiko Eurya; Hungria, Mariangela (Elsevier, 2021)
Short dry spells are an important grain yield constraint in tropical regions. Plant growth-promoting bacteria (PGPB) and their metabolites can mitigate the impact of drought stress by promoting changes in plant metabolism, physiology, and biochemistry. However, the effects of PGPB on soybean [Glycine max (L.) Merril] under drought stress in tropical regions have not been established. The experiments were carried out under tropical field conditions with short dry spells. Therefore, in this study we used a three-factorial trial to evaluate the effects of bacterial consortium consisting of N2-fixing Bradyrhizobium japonicum (strain SEMIA 5079) and Bradyrhizobium diazoefficiens (strain SEMIA 5080), the biocontrol agent Bacillus subtilis (strain QST 713), and the plant growth-promoting Azospirillum brasilense (strains Ab-V5 and Ab-V6) with or without application of microbial secondary metabolites (MSM, rhizobial metabolites enriched in lipo-chitooligosaccharides (LCOs)) during two growing seasons. Photosynthetic pigments, gas exchange parameters, antioxidant enzyme activity and proline concentrations in leaves, nodulation, plant growth development and grain yield were evaluated. The bacterial consortium comprising Bradyrhizobium spp., A. brasilense strains and MSM application increased the contents of chlorophyll a (14.5 %), chlorophyll b (30.8 %), total chlorophyll (17.2 %), and total carotenoids (27.3 %) compared with Bradyrhizobium spp. treatment alone. This consortium also increased the net photosynthetic rate (17.7 %), stomatal conductance (56.5 %), internal CO2 concentration in the substomatal chamber (8.3 %), and transpiration (44 %) compared with plants that received the standard inoculation (Bradyrhizobium spp. only), while reducing the leaf contents of hydrogen peroxide (−18.8 %) and proline (−29.4 %), lipid peroxidation (−15.9 %), and the activities of superoxide dismutase (−18.2 %), catalase (−21.2 %), and ascorbate peroxidase (−19.1 %). Taken together, the results indicate that a beneficial bacterial consortium comprising Bradyrhizobium spp. and A. brasilense strains combined with MSM application can alleviate oxidative damage during dry spells. Furthermore, this consortium improved soybean nodulation, plant growth development, and grain yield by up to 12.2 %.
Keywords: Antioxidant metabolism; Glycine max; Photosynthesis; Plant growth-promoting bacteria; Water deficit